The Evolution of Gajahmungkur Paleovolcano, Wonogiri, Central Java, as A Reference to Revize the Terminology of âOld Andesite Formationâ - Syafri, Ildrem; Sudradjat, A.; Sulaksana, Nana; Hartono, G. (Indonesian Journal on Geoscience, 2010)
DOI:Â 10.17014/ijog.v5i4.109Gajahmungkur is a Tertiary paleovolcano located in Wonogiri Regency, Central Java. The volcanic product of this volcano are widely distributed and composed of important elements of the stratigraphic sequence in the Southern Mountain area. The volcanic products so far have been simply classified as âOld Andesite Formationâ which apparently is not in line with the stratigraphic code and the Indonesian Stratigraphic Code. The description of paleovolcano therefore might contribute to the revision of the âOld Andesite Formationâ. The evolution of Gajahmungkur paleovolcano commenced with the formation of a submarine volcano, and then at the second phase a composite volcano emerged above sea level forming a volcano island. The third phase was the self destruction resulting in a formation of a caldera. Pumiceous components dominated the products. At the fourth phase, the activities began to decline producing more basaltic rocks. The statistical analysis of the interrelation between various physical properties of the clastic rocks leads to the identification of volcanic facies and the location of the paleovolcano vent.